MORPHOLOGICAL CHANGES OF THE SPLEEN IN AUTOIMMUNE DISEASES: A LITERATURE REVIEW - Boymurodova Mekhriniso Nurmurodovna; Boltayeva Donokhon Bakhtiyorovna (Web of Journals Publishing, 2025)
Autoimmune diseases (AIDs) can significantly impact spleen morphology due to chronic immune activation and dysregulation. This review examines the morphological changes in the spleen associated with various autoimmune disorders, including rheumatoid arthritis, autoimmune thyroiditis, and autoimmune blistering diseases. Recent histopathological and imaging studies indicate common alterations such as splenomegaly, follicular hyperplasia, and changes in white pulp architecture. Understanding these morphological modifications provides valuable insights into disease progression, potential diagnostic markers, and therapeutic implications. Further research is needed to explore the clinical significance of spleen alterations in autoimmune conditions.
Keywords: Autoimmune diseases, spleen morphology, splenomegaly, follicular hyperplasia, histopathology, immune dysregulation, rheumatoid arthritis, autoimmune thyroiditis, diagnostic markers, systemic inflammation.